Seeds of Change: Transforming African Agriculture Together - International Institute of Tropical Agriculture (International Institute of Tropical Agriculture, 2025)
From Côte d’Ivoire to Nigeria, voices were united around a common goal: to innovate, collaborate, and grow. The event spotlighted the IITA e-catalog, a digital platform mapping out farmer-ready technologies—from climate-smart practices to productivity-boosting toolkits. Through live demonstrations, the delegates from Côte d’Ivoire explored digital solutions tailored for farming, processing, climate resilience, and strategic planning.